Crossrail Project : infrastructure design and construction. Volume 5 - Williams, Rhys Vaughan; Black, Mike (Engineering geologist) (ICE Publishing, 2018)
The construction of the Crossrail project began at North Dock in Canary Wharf in May 2009 and it has been one of the largest single infrastructure investments undertaken in the UK to date. Consisting of 21 kilometres of new twin-bore tunnels and 10 new world-class stations in central London connecting to upgraded lines, the line will provide essential new services to the east and west of the UK capital. Crossrail Project: Infrastructure Design and Construction - Volume 5 contains 21 new papers submitted to Crossrail's Technical Papers Competition. Contributions have come from consultants, contractors, suppliers and third-party stakeholders, all of whom have been involved in the Crossrail project. The papers cover a variety of disciplines including fire safety, sustainability, engineering design, reliability and many more.